Appraising the Obligations of the Nigerian State in Achieving Zero Hunger - Shaibu, Enemona Gabriel (ABUAD Law Journal, 2023)
Nigeria as a Nation-State is saddled with certain obligations to her citizens, some are justiciable and others are not. The Nigerian-State being a member of the United Nations adopted the Sustainable Development Goals (SDGs) in September, 2015. There are 17 SDGs and one of which is SDG-2, Zero hunger. The primary targets of SDG-2 are aimed to end hunger, achieve food security, improve nutrition and promote sustainable agriculture worldwide, by the year 2030. Nigeria has not fared well under the recently published Global Hunger Index scores as it falls under the group of States faced with serious hunger, despite its efforts in domesticating and implementing the SDGs, particularly, SDG-2 through various policy and institutional frameworks. This paper, inter alia appraises the obligations of the Nigerian-State to her citizens, the various policy and institutional frameworks domesticated in Nigeria in order to achieve zero hunger by the year 2030. Being a paper that is situated within the right to food paradigm, it adopts the doctrinal and analytical approach, relying on primary data like the 1999 Constitution of the Federal Republic of Nigeria and other conventions, secondary data like articles and opinions of jurists on the subject matter. It is the finding inter alia that it will be very difficult if not impossible for Nigeria to achieve zero hunger by the year 2030. The paper concludes inter alia that a well-coherent legal framework for right to food is vital in addressing the serious prevalence of hunger and looming food insecurity in Nigeria.